Pre-Treatment Breast Cancer Patients Show Neural Differences in Frontal Alpha Asymmetry. (March 2023) - Prashad, Neelam; Melara, Robert D.; Root, James C.; Ahles, Tim A.
Cognitive impairment has been observed consistently in a subset of breast cancer survivors. Yet, still unknown is whether neural and behavioral effects of cancer exist prior to treatment, which may contribute to later cognitive decline. The current study investigated pre-treatment differences in attention performance and frontal alpha asymmetry (FAA), an established neural index of inhibitory control, in non-metastatic breast cancer patients ( n  = 42) compared with healthy controls ( n  = 28). We additionally investigated whether differences between groups appear in specific cuing conditions and across different stages of information processing. Participants underwent EEG while completing the Attention Network Task (ANT), a cognitive measure of alerting, orienting, and inhibitory control of attention. Results revealed no behavioral differences between patients and controls but significantly greater right-hemisphere alpha activity (reduced inhibitory control) in patients, particularly to uninformative (no cue, double cue) versus informative (valid cue) cues and in later stages of information processing (400–800 ms post-stimulus). Results suggest neural differences between groups to uncertain stimulus environments that have yet to manifest behaviorally. FAA may thus serve as a unique neural correlate that could potentially be used to predict later cognitive decline.